2019
DOI: 10.3390/toxins11030180
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Mycotoxins during Fermentation of Whole Grain Sorghum to Whole Grain Ting (a Southern African Food)

Abstract: Mycotoxins are fungal secondary metabolites that pose health risks to exposed individuals, requiring necessary measures to reduce them. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS), mycotoxins were quantified in whole grain sorghum and ting subsequently derived from two sorghum varieties (high and low tannin). The whole grain (WG) ting samples were obtained by fermenting sorghum with Lactobacillus fermentum strains (FUA 3165 and FUA 3321). Naturally (spontaneously) fermented WG-ting under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The content of mycotoxins (found in the whole grain of sorghum raw material) was decreased in all fermented samples. More specifically, L. fermentum FUA 3321 reduced the studied mycotoxins by up to 98% [16]. Moreover, traditional fermentation processes reduced the mycotoxin content of kunu-zaki and pito (two popular traditional cereal-based African beverages) by 59% and 99%, respectively [17].…”
Section: Impact On Food Safety and Shelf-life Extensionmentioning
confidence: 98%
See 1 more Smart Citation
“…The content of mycotoxins (found in the whole grain of sorghum raw material) was decreased in all fermented samples. More specifically, L. fermentum FUA 3321 reduced the studied mycotoxins by up to 98% [16]. Moreover, traditional fermentation processes reduced the mycotoxin content of kunu-zaki and pito (two popular traditional cereal-based African beverages) by 59% and 99%, respectively [17].…”
Section: Impact On Food Safety and Shelf-life Extensionmentioning
confidence: 98%
“…Phenolic components, which are secondary plant metabolites, are also found in notable amounts in cereals [60]. The metabolic pathways (shikimate, phenylpropanoid) for their biosynthesis involve many biomolecules like acetyl CoA, malonyl CoA, pyruvate, acetate, and some amino acids (phenylalanine and tyrosine) [16]. Their beneficial properties in human health (anti-diabetic, anti-cancer, anti-inflammatory, anti-microbial, anti-oxidant, as well as neuro-, cardio-, and hepato-protective function) are attributed to their ideal chemical structure, which promotes electron transfer or hydrogen donation from the hydroxyl groups of their aromatic ring and thereby exhibit free radical scavenging activities and metal-chelating potential [60,62,63].…”
Section: Phenolic Componentsmentioning
confidence: 99%
“…Sorghum fermentation usually results in changes to and the subsequent improvement of nutritional qualities, taste, shelf life, aroma and structural modification. Similar to other cereal fermentation processes, fermentation of sorghum leads to a modification (increase/decrease) of inherent metabolites and constituents (Figure 2), activation of enzymes, decrease in pH levels, increased metabolic activities and microbial actions with a consequent decrease in ANFs, detoxification and degradation of contaminants [9,11,17,[145][146][147][148][149][150][151][152][153]. These modifications are, in part, due to proteolysis, with the possible formation of monomers from large molecules.…”
Section: Sorghum Fermentationmentioning
confidence: 99%
“…An appropriate assessment of the risk associated with these reported pathogens should, however, be carefully considered, as cell counts and/or the frequency of their presence would indicate if they really are of concern in these foods. Judging from numerous studies and reviews that have shown that fermentation and LABs are capable of reducing/degrading toxins and contaminants in foods [147,150,151,153,[172][173][174][175][176], it could be postulated that the levels found could either be 'residues' and or 'left-overs' of the fermentation process. The role of post contamination of these products should also not be ruled out as a possible source of these opportunistic microorganisms.…”
Section: Safety Of African Sorghum Fermented Foodsmentioning
confidence: 99%
“…The climatic and environmental conditions in Southern Africa are characterised by high temperatures, humidity, uneven rainfall and constant occurrences of drought. These conditions are suitable for mycotoxigenic fungal growth and proliferation (1)(2)(3)(4). Seventy percent of Botswana's landmass is occupied by the Kalahari Desert, leaving the country with limited supplies of water, high temperatures and dry seasons.…”
Section: Introductionmentioning
confidence: 99%